Efek Konsumsi Daging Kambing terhadap Tekanan Darah - Afid, Muhammad Dimas; Nurmasitoh, Titis (Kes Mas: Jurnal Fakultas Kesehatan Masyarakat, 2016)
Background: The high prevalence of hypertension and its complications made the society more awareness. The people do some efforts to control blood pressure by limit the consumption of the food that could arise blood pressure such as mutton. The aim of this research was to determine the differences of average blood pressure before and after mutton consumption. Method: This research was a part of experimental method. The research was conduct at Belang Wetan, Klaten Utara. The sample of this research were 42 people with inclusion and exclusion criteria. The samples are chosen by consecutive sampling method. The blood pressure measured before mutton consumption and after 60 minutes after consuming with sphigmomanometer. Results: The average of systolic blood pressure before and after consumption was 105.48±10.41 113.76±7.6 mmHg into (p=0.00). While the average diastolikic blood pressure before and after mutton consumption was 67.62±7.9 to 75±5.52 mm Hg (p=0.00). Conclusion: There is a difference of average blood pressure before and after mutton consumption increasing blood pressure.